METHODS OF FINANCING THE ENTERPRISE IN MODERN UZBEKISTAN’S PRACTICE - Fayzieva Nilufar Shukhrat Qizi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Today, the countries of the world are looking for different ways of economic development and use them in the development of the country. It is very important to study foreign experience in this direction. This article presents the Uzbekistan’s method of financing entrepreneurship. In Uzbekistan, there are various ways of financing. It is necessary to choose the most effective and introduce them in our country.